2016
DOI: 10.1111/ipd.12264
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of sleep bruxism can assist in the detection of cases of verbal school bullying and measure the life satisfaction of adolescents

Abstract: Possible sleep bruxism can assist in the detection of adolescents involved in school bullying at school in the roles of victim and victim/perpetrator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 24 publications
0
44
0
Order By: Relevance
“…Althogh present study had had some limitations, such as an absence of control group, results presents positive statistical associations with clinical signs, which is important to evaluate at clinical practice. SB diagnosis is still controvesal in literature, both in children and adults 30 , 31 , 32 ) . Researches pointed to polysomnography as the gold standard for the SB diagnosis 32 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Althogh present study had had some limitations, such as an absence of control group, results presents positive statistical associations with clinical signs, which is important to evaluate at clinical practice. SB diagnosis is still controvesal in literature, both in children and adults 30 , 31 , 32 ) . Researches pointed to polysomnography as the gold standard for the SB diagnosis 32 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Besides these factors, studies have investigated the association between economic status and SB, revealing controversial results. While in a study conducted with Brazilian schoolchildren, a higher frequency of SB among participants from disadvantaged families was observed (9), in another research, it was concluded that adolescent SB was more frequent among adolescents from a higher economic class (11). This lack of evidence on the association between economic status and SB was emphasised in a systematic review, indicating the need for further investigation.…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, there was no significant association between probable sleep bruxism and the stress of the mothers and the children. This study broadens knowledge on factors associated to probable sleep bruxism and can serve as a guide for decision‐making related to the prevention, diagnosis, and treatment of sleep bruxism in schoolchildren. Headache, muscle pain, behavioural problems, and poor sleep quality are frequent consequences of SB. Socio‐economic factors, psychological factors (anxiety, stress, personality traits, and attention‐deficit hyperactivity disorder), verbal school bullying, and respiratory disorders have been associated with the prevalence of SB.…”
Section: Introductionmentioning
confidence: 99%
“…1 Headache, muscle pain, 2,3 behavioural problems, and poor sleep quality 4,5 are frequent consequences of SB. Socioeconomic factors, psychological factors (anxiety, stress, personality traits, and attention-deficit hyperactivity disorder), [6][7][8] verbal school bullying, 9,10 and respiratory disorders 11 have been associated with the prevalence of SB.…”
Section: Introductionmentioning
confidence: 99%